Patient Risk Factors Associated With 30- and 90-Day Readmission After Cervical Discectomy: A Nationwide Readmission Database Study. Issue 9 (November 2020) - Elsamadicy, Aladine A.; Koo, Andrew B.; Lee, Megan; Freedman, Isaac G.; David, Wyatt B.; Kundishora, Adam J.; Gorrepati, Ramana; Kuzmik, Gregory A.; Camara-Quintana, Joaquin; Qureshi, Tariq; Kolb, Luis; Laurans, Maxwell; et al.
Abstract : Study Design: This is a retrospective cohort study. Objective: The aim of this study was to assess the patient-level risk factors associated with 30- and 90-day unplanned readmissions following elective anterior cervical decompression and fusion (ACDF) or cervical disk arthroplasty (CDA). Summary of Background Data: For cervical disk pathology, both ACDF and CDA are increasingly performed nationwide. However, relatively little is known about the adverse complications and rates of readmission for ACDF and CDA. Methods: A retrospective cohort study was performed using the Nationwide Readmission Database from the years 2013 to 2015. All patients undergoing either CDA or ACDF were identified using the International Classification of Diseases, Ninth Revision, Clinical Modification coding system. Unique patient linkage numbers were used to follow patients and to identify 30- and 31–90-day readmission rates. Patients were grouped by no readmission (Non-R), readmission within 30 days (30-R), and readmission within 31–90 days (90-R). Results: There were a total of 13, 093 index admissions with 856 (6.5%) readmissions [ 30-R: n=532 (4.0%); 90-R: n = 324 (2.5%)] . Both overall length of stay and total cost were greater in the 30-R cohort compared with 90-R and Non-R cohorts. The most prevalent 30- and 90-day complications seen among the readmitted cohorts were infection, genitourinary complication, and device complication. On multivariate regression analysis, age, Medicaid status, medium and large hospital bed size, deficiency anemia, and any complication during index admission were independently associated with increased 30-day readmission. Whereas age, large hospital bed size, coagulopathy, and any complication during the initial hospitalization were independently associated with increased 90-day readmission. Conclusion: Our nationwide study identifies the 30- and 90-day readmission rates and several patient-related risk factors associated with unplanned readmission after common anterior cervical spine procedures. Level of Evidence: Level III. Abstract : Supplemental Digital Content is available in the text.